Teaching as if learning matters : pedagogies of becoming by next-generation faculty - Robinson, Jennifer Meta, 1962-; O'Loughlin, Valerie Dean; Kearns, Katherine; Plummer, Laura (Bloomington, Indiana : Indiana University Press, 2022)
"Teaching is an essential skill in becoming a faculty member in any institution of higher education. Yet how is that skill actually acquired by graduate students? Teaching as if Learning Matters collects first-person narratives from graduate students and new PhDs that explore how the skills required to teach at a college level are developed. It examines the key issues that graduate students face as they learn to teach effectively when in fact they are still learning and being taught. Featuring contributions from over thirty graduate students from a variety of disciplines at Indiana University, Teaching as if Learning Matters allows these students to explore this topic from their own unique perspectives. They reflect on the importance of teaching to them personally and professionally, telling of both successes and struggles as they learn and embrace teaching for the first time in higher education"--
Acknowledgments -- Introduction / Jennifer Meta Robinson, Valerie Dean O'Loughlin, Laura Plummer, and Katherine Kearns -- Part I : My Teaching and My Identity / Valerie Dean O'Loughlin -- 1. Death Studies and Learning Communities: Rethinking Professionalism / by Leslie E. Drane -- 2. Who am I? How I Reconciled My Identity as a Woman in Science and Education through Pedagogy Courses and Evidence-Based Teaching, by Natalie Christian -- 3. The Complexities of Teaching: Navigating Empathy and Authority / Maureen Chinwe Onyeziri -- 4. Disrupting Silence and Positionality: Reframing Visions of Equity in College Teaching / Francesca A. Williamson -- 5. How a Multidisciplinary Doctoral Student Instructor Network Became a Tool for Teaching, Professional Development, and Personal Growth / Keely Cassidy, Laura Clapper, and Alyssa M. Lederer -- 6. Building Confidence and Experience within a Graduate Student Teaching Community / Sarah M. Keesom, Jacquelyn Petzold, and Lisa Wiltbank -- 7. Professorial Power: Or, Limiting My Classroom Control to Create Opportunities for Others / Andrew M. Koke -- Part II : My Students and My Classroom / Laura Plummer -- 8. Forming Community with Students: Eliminating Language Barriers as an International Associate Instructor / Jing Yang -- 9. The Graduate Student Learning Community: A Place to Develop Your Teaching Identity and Authority / Letizia Montroni -- 10. Experimenting with a Flipped-Class Method of Instruction in a Medical Histology Course / Barbie Klein -- 11. Facilitating Learning outside the Classroom: Field Trips and Service-Learning / Elizabeth Konwest -- 12. The Courage to Try Something New: What Collaborative Learning Has Brought to My Classroom and Me / Kristyn E. Sylvia -- 13. Endeavoring a Democratic Pedagogy: Tensions and Possibilities in Ambiguity / Polly A. Graham and Sarah Socorro Hurtado -- 14. Making Students Part of the Conversation / Adam Coombs -- 15. Disarming Student Defensiveness: Slowing Approaching Controversial Topics in the Classroom / Kristen Hengtgen -- 16. The Unpredictability of Teaching and the Helpfulness of Classroom Assessments / Juliane Wuensch -- Part III : My Teaching and My Field / Jennifer Meta Robinson -- 17. A Classroom Ritual, Kairos, and Evidencing Student Learning / Mark S. Nagle -- 18. Of Rich Points and Reflexive Teaching: Minding My Own Social Business as an Anthropology Instructor / J. Christopher Upton -- 19. "If I Have a Role": The Classroom as a Performative Space, by Silja Weber -- 20. Teaching the Physicality of Filmmaking: Learning through the Body in Motion Picture Production / Javier Ramirez -- 21. Engaging College Students Using Story-Structured Lessons: In Search of "Evidence" / Ryan G. Erbe -- 22. Avoiding the Easy Way Out: How We Pushed Ourselves and Our Students to Try Something New / Natalie Christian and Michelle R. Marasco -- 23. Pedagogy Classes: A Space for the Formation of Teaching Philosophies and Collaborative Work among Graduate Students / Jessica Leach, Kristen Hengtgen, and Maksymilian Szostalo -- 24. Critical Thinking and Signature Pedagogies / Mack Hagood -- Part IV : My Journey to My Postgraduate Life / Katherine Kearns -- 25. How Becoming a Critical Friend Can Lead to Academic Fluency / Tyler Christensen -- 26. The Teacher as Student and Student as Teacher: Lessons Learned from Developing, Instructing, and Evaluating a Public Health Pedagogy Course / Alyssa Lederer -- 27. Transitioning from Clinician to Educator: Reflections on Teaching and Learning / Laura J. Carpenter -- 28. Aligning Values, Language, and Practice in the Classroom / Jonathan P. Rossing -- 29. Benefit of the Doubt: Building Confidence, Community, and Courage in the Transition from Graduate School to Faculty Life / Rachel La Touche -- 30. There is No "Right" Road / Lauren Miller Griffith -- 31. The Serendipitous Detour: Finding My Way into Educational Development / Carol S. Sullivan Epilogue Editor and Contributor Biographies -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 12, 2022).
eBooks on EBSCOhost
Keywords: College teachers -- Training of -- United States; Graduate students -- Education -- United States; Universities and colleges -- United States -- Faculty; Universités -- États-Unis -- Corps enseignant; EDUCATION / Learning Styles; College teachers -- Training of; Universities and colleges -- Faculty; United States